Photoreceptor thickness in UK Biobank participants with and without diabetes mellitus - Roomasa Channa; Mozhdeh Bahrainian; Kristen Staggers; Kevin J Schneider (BMJ Open Ophthalmology)
Objective Photoreceptors can be impacted early in diabetes mellitus (DM). The primary goal of this study was to determine if having DM and no/mild diabetic retinopathy (DR) affected photoreceptor layer thickness.Methods and analysis Participants from the UK Biobank database who underwent fundus photographs and macula-centred spectral domain-optical coherence tomography were considered for inclusion in the study. Multivariable linear regression models were used to compare photoreceptor thickness between participants with DM (no/mild DR) and without DM after adjusting for confounders. Secondary analyses investigated factors associated with photoreceptor thickness among participants with DM (no/mild DR).Results 64 237 participants without DM and 3832 with DM were included. Among those with DM, 2683 had no/mild DR. The inner segment/outer segment (IS/OS) photoreceptor junction was significantly thinner in participants with DM (no/mild DR) compared with those without DM (−0.06 µm, 95% CI −0.10 to –0.03). The OS photoreceptor layer was thinner in participants with DM (no/mild DR) compared with those without DM (−0.14 µm, 95% CI −0.19 to –0.08). Among participants with DM (no/mild DR), being male was associated with thinner IS/OS (p<0.001) and higher A1c level was associated with thinner OS (p=0.02). Thicker OS layer was associated with higher high-density lipoprotein (p<0.001), male gender (p<0.001) and higher spherical equivalent (p=0.005).Conclusions We found photoreceptor layers to be thinner in participants with DM (no/mild DR) compared with those without DM. Limitations include the absence of additional imaging such as angiography to evaluate the retina for early vascular changes or choroidal imaging to study the potential impact of the choroid on photoreceptors. Overall, our findings suggest that changes in photoreceptors may occur prior to evidence of more than mild DR on fundus photographs.